Identification of gut dysbiosis in axial spondyloarthritis patients and improvement of experimental ankylosing spondyloarthritis by microbiome-derived butyrate with immune-modulating function - Min, Hong Ki; Na, Hyun Sik; Jhun, JooYeon; Lee, Seon-Yeong; Choi, Sun Shim; Park, Go Eun; Lee, Jeong Su; Um, In Gyu; Lee, Seung Yoon; Seo, Hochan; Shin, Tae-Seop; Kim, Yoon-Keun; et al. (Frontiers in Immunology, 2023)
Dysbiosis is an environmental factor that affects the induction of axial spondyloarthritis (axSpA) pathogenesis. In the present study, we investigated differences in the gut microbiota of patients with axSpA and revealed an association between specific gut microbiota and their metabolites, and SpA pathogenesis. Using 16S rRNA sequencing data derived from feces samples of 33 axSpA patients and 20 healthy controls (HCs), we examined the compositions of their gut microbiomes. As a result, axSpA patients were found to have decreased α-diversity compared to HCs, indicating that axSpA patients have less diverse microbiomes. In particular, at the species level, Bacteroides and Streptococcus were more abundant in axSpA patients than in HCs, whereas Faecalibacterium (F). prausnitzii, a butyrate-producing bacteria, was more abundant in HCs. Thus, we decided to investigate whether F. prausnitzii was associated with health conditions by inoculating F. prausnitzii (0.1, 1, and 10 μg/mL) or by administrating butyrate (0.5 mM) into CD4+ T cells derived from axSpA patients. The levels of IL-17A and IL-10 in the CD4+ T cell culture media were then measured. We also assessed osteoclast formation by administrating butyrate to the axSpA-derived peripheral blood mononuclear cells. The CD4+ IL-17A+ T cell differentiation, IL-17A levels were decreased, whereas IL-10 was increased by F. prausnitzii inoculation. Butyrate reduced CD4+ IL-17A+ T cell differentiation and osteoclastogenesis. We found that CD4+ IL-17A+ T cell polarization was reduced, when F. prausnitzii or butyrate were introduced into curdlan-induced SpA mice or CD4+ T cells of axSpA patient. Consistently, butyrate treatment was associated with the reduction of arthritis scores and inflammation levels in SpA mice. Taken together, we concluded that the reduced abundance of butyrate-producing microbes, particularly F. prausnitzii, may be associated with axSpA pathogenesis.